PROFESSOR DR. ABDUL RAHMAN MOHAMED APPOINTED AS DEPUTY VICE-CHANCELLOR (JIM) USM - PROFESSOR DATO' DR. MUHAMAD JANTAN TO RESUME AS DEPUTY VICE-CHANCELLOR FOR R&I - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 May 2016 – A Top Research Scientist Malaysia (TRSM) and an expert in Reaction Engineering & Catalysis, Air Pollution Monitoring and Control, Fuel Technology and Nanotechnology, Professor Dr. Abdul Rahman Mohamed, 52, has been appointed by the Ministry of Higher Education as the Deputy Vice-Chancellor (Industry and Community Network/JIM) of Universiti Sains Malaysia (USM) for the next three years effective 1 May 2016.